Breaking the ‘forever’ bond: photocatalytic degradation of per- and polyfluoroalkyl substances using ternary photocatalysts - Uday Shashikumar; Himanshi Goel; Ishika Rana; Pei-Chien Tsai; Kiran B. Manjappa; Phuong V. Pham; Gangadhar Andaluri; Kumar Rakesh Ranjan; Yuan-Chung Lin; Vinoth Kumar Ponnusamy; Po-Chin Huang (Reviews in Environmental Science and Bio/Technology, 2025)

Spatial Heterogeneity in Health Risk Assessment of Heavy Metals During North-East Monsoon and South-West Monsoon over India - Martina Rani; Sakshi Ahlawat; N. Vijayan; Lokesh Yadav; Tirthankar Banerjee; Abhijeet Chatterjee; Manpreet Singh Bhatti; Trupti Das; Amit Dhir; Sangita Goel; Altaf Husain Khan; Ravindra Khaiwal; et al. (Aerosol Science and Engineering, 2025)

Innovations in tannery wastewater management: a review of zero liquid discharge technology - A. Pundir; M. S. Thakur; B. Goel; Radha; A. Kumar; S. Prakash; M. Thakur; M. Kumar (International Journal of Environmental Science and Technology, 2025)

Evaluation of environmental impacts of mobile phones in India using life cycle assessment technique - D. Dutta; VR. Sankar Cheela; B. Dubey; S. Kumar; S. Goel (International Journal of Environmental Science and Technology, 2025)

Estimating soil mineral nitrogen from data-sparse field experiments using crop model-guided deep learning approach - Rishabh Gupta; Satya K. Pothapragada; Weihuang Xu; Prateek Kumar Goel; Miguel A. Barrera; Mira S. Saldanha; Joel B. Harley; Kelly T. Morgan; Alina Zare; Lincoln Zotarelli (Computers and Electronics in Agriculture, 2024)

Study of pathogenic T-helper cell subsets in Asian Indian patients with Takayasu arteritis - P. M. Punithavathy; Ramesh Babu Telugu; Vinay Murahari Rao; Savit B. Prabhu; Jayakanthan Kabeerdoss; Chanduni Syed; George Joseph; Debashish Danda; Meera Thomas; Ruchika Goel (Immunologic Research, 2024)

Site-specific characterisation of hydrogeological parameters for low-level solid radioactive waste disposal facility at Tarapur, India - Shelly Goel; Manish Chopra; Aditi C Patra; Faby Sunny; G Ganesh; R B Oza; M S Kulkarni (Journal of Earth System Science, 2023)

Transcriptome Analysis of Podoscypha petalodes Strain GGF6 Reveals the Diversity of Proteins Involved in Lignocellulose Degradation and Ligninolytic Function - Rishi Mahajan; B. Shenu Hudson; Deepak Sharma; Vaishnavi Kolte; Gaurav Sharma; Gunjan Goel (Indian Journal of Microbiology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Characteristics of indoor air pollutants and estimation of their exposure dose - Sangita Ghatge Goel; Shashank Somwanshi; Sanket Mankar; B. Srimuruganandam; Rajesh Gupta (Air Quality, Atmosphere & Health, 2021)

Assessment of Soil Chemical Quality, Soil Microbial Population and Plant Growth Parameters Under Organic and Conventional Rice–Wheat Cropping System - Reeta Goel; Prasenjit Debbarma; Puja Kumari; Deep Chandra Suyal; Saurabh Kumar; B. S. Mahapatra (Agricultural Research, 2021)

Protein Kinase Inhibitors Arrested the In-Vitro Growth of Theileria equi - Jyotika Yadav; Praveen Goel; Kruti Debnath Mandal; Rahul Yadav; Naveen Kumar; Rajender Kumar; B. N. Tripathi; Sanjay Kumar (Acta Parasitologica, 2020)

Endocellulase Production by Cotylidia pannosa and its Application in Saccharification of Wheat Bran to Bioethanol - Deepika Sharma; Amit Sud; Saurabh Bansal; Rishi Mahajan; B. M. Sharma; Rajinder Singh Chauhan; Gunjan Goel (BioEnergy Research, 2018)

Scale dependency of dynamic relative permeability–satuartion curves in relation with fluid viscosity and dynamic capillary pressure effect - Gaurav Goel; Luqman K. Abidoye; Bhagu R. Chahar; Diganta B. Das (Environmental Fluid Mechanics, 2016)

Unraveling the cytotoxic potential of Temozolomide loaded into PLGA nanoparticles - Darshana S Jain; Rajani B Athawale; Amrita N Bajaj; Shruti S Shrikhande; Peeyush N Goel; Yuvraj Nikam; Rajiv P Gude (DARU Journal of Pharmaceutical Sciences, 2014)
Background Nanotechnology has received great attention since a decade for the treatment of different varieties of cancer. However, there is a limited data available on the cytotoxic potential of Temozolomide (TMZ) formulations. In the current research work, an attempt has been made to understand the anti-metastatic effect of the drug after loading into PLGA nanoparticles against C6 glioma cells. Nanoparticles were prepared using solvent diffusion method and were characterized for size and morphology. Diffusion of the drug from the nanoparticles was studied by dialysis method. The designed nanoparticles were also assessed for cellular uptake using confocal microscopy and flow cytometry. Results PLGA nanoparticles caused a sustained release of the drug and showed a higher cellular uptake. The drug formulations also affected the cellular proliferation and motility. Conclusion PLGA coated nanoparticles prolong the activity of the loaded drug while retaining the anti-metastatic activity.

Allocation in life cycle inventory: partial set of solutions to an ill-posed problem - Nathan B. Cruze; Prem K. Goel; Bhavik R. Bakshi (The International Journal of Life Cycle Assessment, 2014)

Revisiting least squares techniques for the purposes of allocation in life cycle inventory - Nathan B. Cruze; Prem K. Goel; Bhavik R. Bakshi (The International Journal of Life Cycle Assessment, 2014)

Water pollution of Sabarmati River—a Harbinger to potential disaster - Soumya Haldar; Subir Kumar Mandal; R. B. Thorat; Sangita Goel; Krushnakant D. Baxi; Navalsang P. Parmer; Vipul Patel; S. Basha; K. H. Mody (Environmental Monitoring and Assessment, 2014)

Occurrence and distribution of selected heavy metals and boron in groundwater of the Gulf of Khambhat region, Gujarat, India - Devang Upadhyaya; Mayur D. Survaiya; Shaik Basha; Subir K. Mandal; R. B. Thorat; Soumya Haldar; Sangita Goel; Himal Dave; Krushnakant Baxi; Rohit H. Trivedi; Kalpana H. Mody (Environmental Science and Pollution Research, 2014)

Genetic structure and diversity of India hybrid tea - S. N. Raina; P. S. Ahuja; R. K. Sharma; S. C. Das; P. Bhardwaj; R. Negi; V. Sharma; S. S. Singh; R. K. Sud; R. K. Kalia; V. Pandey; J. Banik; et al. (Genetic Resources and Crop Evolution, 2012)

Overexpression of osmotin gene confers tolerance to salt and drought stresses in transgenic tomato (Solanum lycopersicum L.) - D. Goel; A. K. Singh; V. Yadav; S. B. Babbar; K. C. Bansal (Protoplasma, 2010)

Development of isopluvial map using L-moment approach for Tehri-Garhwal Himalaya - S. Sarkar; N. K. Goel; B. S. Mathur (Stochastic Environmental Research and Risk Assessment, 2010)

Activation and regulation of Toll-Like Receptors (TLRs) by helminth parasites - Priyanka Goel Venugopal; Thomas B. Nutman; Roshanak Tolouei Semnani (Immunologic Research, 2009)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Individual and combined effect of (±)-α-hydrastine and (±)-β-hydrastine on spore germination of some fungi - M. Goel; U. P. Singh; R. N. Jha; V. B. Pandey; M. B. Pandey (Folia Microbiologica, 2003)

Effect of Immunization with Plasmid DNA Encoding for Rinderpest Virus Matrix Protein on Systemic Rinderpest Virus Infection in Rabbits - B. Pahar; B. Sharma; A.C. Goel (Veterinary Research Communications, 2002)

Immunization with a plasmid DNA expressing rinderpest virus hemagglutinin protein protects rabbits from lethal challenge - A. Joshi; B. Sharma; A. C. Goel; B. Mondal (Archives of Virology, 2002)

Prophylactic oophorectomy in Ontario - L. Elit; B. Rosen; V. Goel; L. McLaughlin; M. K. F. Fung; J. Shime; S. Narod (Familial Cancer, 2001)

Evidence for new nuclear and mitochondrial genome organizations among high-frequency somatic embryogenesis-derived plants of allotetraploid Coffea arabica L. (Rubiaceae) - V. Rani; K. P. Singh; B. Shiran; S. Nandy; S. Goel; R. M. Devarumath; H. L. Sreenath; S. N. Raina (Plant Cell Reports, 2000)

Attenuation of changes in sarcoplasmic reticular gene expression in cardiac hypertrophy by propranolol and verapamil - Satoshi Takeo; Adel B. Elmoselhi; Raj Goel; Emmanuelle Sentex; Jingwei Wang; Naranjan S. Dhalla (Molecular and Cellular Biochemistry, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)